Bilateral Ovarian Malakoplakia: Case Report and Review of the Literature With Clinical and Diagnostic Considerations. (January 2021) - Carbone, Riccardo; Bonometti, Arturo; Cassani, Chiara; Lucato, Elena; Rossi, Margherita; Spinillo, Arsenio; Paulli, Marco; Cesari, Stefania
Abstract : Malakoplakia is a rare condition in which histiocytic cells accumulate within different organs and tissues, sometimes mimicking neoplasia. Gynecologic involvement is extremely rare and therefore may cause relevant diagnostic confusion for both clinicians and pathologists. In this paper, we described the seventh case of ovarian malakoplakia, and we reviewed the literature to compare it with the previously reported ones. Moreover, we investigated the histologic and molecular differential diagnosis of malakoplakia, with special attention to other histiocytic disorders of gynecologic interest. Finally, we discussed the most relevant points with regard to possible pathogenesis and management. Malakoplakia often represents a forgotten entity that should be remembered preoperatively, when approaching a possible gynecologic neoplasia. Moreover, it is of remarkable importance to differentiate malakoplakia from multisystem histiocytosis involving gynecologic organs. All this would prevent misdiagnosis and overtreatment of such a rare but benign condition.